The Influence of Responsibility on the Job Commitment of Public Elementary School Principals in East Jakarta - Utami, Purwani Puji; Vioreza, Niken; Nugraheny, Devita Cahyani; Alghadari, Fiki (LPPM STKIP Kusuma Negara, 2024)
Lack of responsibility might determine leaders’ dedication or commitment to making progress at their workplace. This research aims to investigate the effect of job responsibility on the job commitment of public elementary school principals. The sample involved 76 principals in East Jakarta who were selected using a random sampling technique. The method used in this research was surveys and the data were analyzed using path analysis. The results showed a positive direct effect of job responsibility on the principals’ job commitment. The study’s findings concluded that the job commitment of school principals can be promoted by improving their job responsibilities.